Structural influences on groundwater circulation in the Makgadikgadi salt pans of Botswana? Implications for martian playa environments - Schmidt, G.; Luzzi, E.; Franchi, F.; Selepeng, A. T.; Hlabano, K.; Salvini, F. (Frontiers in Astronomy and Space Sciences, 2023)
Across the surface of Mars, evidence of past lacustrine and evaporitic environments has been found within basins and craters, where often layered sedimentary deposits and hydrated minerals are observed. However, the intensity, duration, and precise phases of aqueous processes during their deposition remain unresolved mostly for our inability to model subsurface structures. Although several geological processes and locations on Earth have been previously proposed as examples to describe these deposits on Mars, we lack a strong visualization of what water activity might have looked like during evaporitic stages within basins and craters. Here we propose to investigate the shallow subsurface of the Makgadikgadi salt pans of Botswana as a potential analog for understanding groundwater upwelling on Mars. The pans are found within the Makgadikgadi Basin, a depression located at the southwestern end of a northeast-southwest set of graben linked with the East African Rift. The Makgadikgadi Pans are evaporitic environment rich in hydrated minerals and groundwater activity. The purpose of this work is to identify buried faults and areas of relative water saturation within the lacustrine sediment of the Makgadikgadi Basin by means of electrical resistivity surveys. This work represents the first electrical resistivity survey of the basin floor which provides a precursory investigation of the relationship between groundwater, faults, basement depth, and the lacustrine sediments. We present four electrical survey lines from different locations in the pans which reveal distinct sedimentary units. Several faults are inferred from the vertical displacement of these units and accompanying low resistivity where displacement is observed. These results provide a framework for visualizing the sedimentary sequences of infilled basins and craters on Mars, which can broaden the ongoing discussion of hydrogeological processes that were active in the planet’s past. We propose Meridiani Planum, as well as Oyama and Becquerel crater of Arabia Terra as locations to establish this framework. Since such processes are still ongoing in the Makgadikgadi Basin, imaging the subsurface of the pans helps explain the formation of layered and salty deposits on the surface of Mars, how they may have interacted with flowing water, and whether they might have hosted life.